Answer:
y =
x² + x - 4
Explanation:
Given roots x = a and x = b, then the factors are
(x - a) and (x - b)
The function is then the product of the factors
y = a(x - a)(x - b) ← where a is a multiplier
Given roots are x = - 4 and x = 2 then the factors are
(x - (- 4)) and (x - 2), that is (x + 4) and (x - 2), thus
y = a(x + 4)(x - 2)
To find a substitute (6, 20) into the function
20 = a(6 + 4)(6 - 2) = a(10)(4) = 40a ( divide both sides by 40 ), thus
a =
=
y =
(x + 4)(x - 2) ← expand factors
=
(x² + 2x - 8) ← distribute
y =
x² + x - 4